WILL ABUSIVE SUPERVISION EFFECTON EMPLOYEE TURNOVER, PERFORMANCE AND COMMITMENT? EMOTIONAL EXHAUSTION AS A MEDIATOR - Joseph Antono; Eunike Yudit Gonzaga; Ahmad Shaddiqi; Nikodemus Wijaya (Jurnal Riset Bisnis dan Manajemen, 2023)
Supervisor behaviors have implications on employee emotion. Ideally, a supervisor can create a conducive working environment that supports the positive psychological states of employees. Emotional exhaustion is one phenomenon that becomes a focus of this study. In this research employee emotion exhaustion can be related to abusive supervision. This study proposes to investigate the relationship among abusive supervision, emotional exhaustion, turnover intention, work performance, and organizational commitment. Emotional exhaustion is treated as a mediator. A total of 161 employees were involved as participants. Results showed that (1) abusive supervision was positively related to emotional exhaustion, (2) emotional exhaustion was positively related to turnover intention, and (3) emotional exhaustion was negatively related to work performance and organizational commitment. In addition, emotional exhaustion could mediate the relationships between the independent variable and the three dependent variables. Contributions of this work are addressed. The limitations of the study were also described.